Digital human modeling and applications in health, safety, ergonomics and risk management : Posture, motion and health : 11th International Conference, DHM 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: Posture, motion and health : 11th International Conference, DHM 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part I (2020) - Unknown
No abstract available